Aktivitas Antibakteri Ekstrak Etanol Pisang Awak (Musa paradisiaca cv. Awak) terhadap Pertumbuhan Bakteri Shigella flexneri ATCC 12022 secara In Vitro: Aktivitas Antibakteri Ekstrak Pisang Awak (Musa paradisiaca cv. Awak) terhadap Pertumbuhan Shigella flexneri ATCC 12022 secara In Vitro - Risza Lailiana Makrifah; Erny Qurotul Ainy (Bioveritas Journal of Biology, 2022)
Shigellosis is an infectious disease that is mainly caused by Shigella flexneri. Antibiotics resistance became the reason to develop an alternative of plant-based antibacterial, one of them is made from pisang awak. The utilization of pisang awak is still rare, it makes the economical value of Pisang awak is low. Several studies have revealed that several varieties of bananas contain antibacterial bioactive compounds in form of saponins, tannins, and alkaloids. This research aimed to determine the antibacterial potential of ethanol extract of various parts of pisang awak organs against the growth of S. flexeneri, as well as knowing the value of Minimum Inhibitory Concentration (MIC) and Minimum Killing Concentration (MKC). Antibacterial activity test were performed using disc diffusion (Kirby Bauer) and dilution method with various concentrations at 2.5%, 5%, 7.5%, 10%, 12.5%, 15%, and 17.5% (b/v). the result showed that the stem and leaves extract of Pisang Awak had an antibacterial activity which was indicated by the diameter of the inhibitory level of 20.98 mm dan 20.91 mm respectively. The MIC value of the stem and leaves was 2.5% (b/v), while the MIC value of the two extracts was not obtained.